Crimes In Information and Communication Technology Against the Environment - Rizky, Fajar Khaify (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research will discuss the substance relating to environmental crimes contained in Law No. 32 on Environmental Protection and Management, whether Cyber Crime in its application is related to environmental crimes that cause pollution and / or environmental damage, because in the process of activity and management of natural resources whose perpetrators are subjects of environmental law in the form of companies in the form of legal entities or non-legal entities will utilize technology and information via the internet for their activities. This research uses normative legal research methods with qualitative methods. Cybercrime is related to environmental crimes contained in Law Number 32 of 2009 concerning Environmental Protection and Management, including environmental crimes committed by corporations, and falsification of data via the internet on manifest waste and other polluting materials that result in losses to the community and the environment